BAGAIMANA RETURN ON ASSET DAN CASH RATIO YANG BAIK MEMPENGARUHI KEBIJAKAN DIVIDEN - Modjaningrat, Radina; Bahri, Syaiful (LPPM UNISDA, 2025)
The research aims to determine and analyze the influence of return on assets and cash ratio on dividend policy. Causal associative research with the population of mining sub-sector companies on the Indonesia Stock Exchange in 2021-2023. The research sample is based on criteria with secondary data types. Based on the test results, ROA and CR have a positive effect on dividend policy. The dividend policy in the form of dividend distribution is determined by the level of profitability, while the dividend policy in the form of dividends is determined by the presence of cash. The research results also prove that the sample entities have made profitability and cash levels the basis for dividend policy. Further research develops by adding other variables that form the basis of dividend policy and allows the use of mediating or moderating variables to improve the quality of research results.